The required solution to the given inequality is x < -14. which is the correct answer would be an option (D).
Inequality is defined as mathematical statements that have a minimum of two terms containing variables or numbers that are not equal.
To solve the inequality x − 2 > 2x + 12, we first need to isolate the x-term on one side of the inequality. We can do this by adding 2 to both sides, which gives us:
x − 2 + 2 > 2x + 12 + 2
x > 2x + 14
Then, we can subtract 2x from both sides to isolate the x-term on the left-hand side:
x - 2x > 2x + 14 - 2x
-x > 14
Finally, we can divide both sides by -1 to get x < -14.
Therefore, the required solution to the given inequality is x < -14.
Learn more about the inequalities here:
#SPJ2
Answer:
x^3-2x^2-5x+6
Step-by-step explanation:
(x-3)(x-1)
(x^2-x-3x+3)(x+2)
x^3+2x^2-4x^2-8x+3x +6
now combine like terms
-8x + 3x = 5x
2x^2-4x^2= -2x^2
Note: The circumference of the earth’s equator is 24,901 miles. 1 mile = 5280 feet
Answer:
Step-by-step explanation:
As we know that:
Sum of the measure of all interior angles of a triangle is always 180°.
Answer:
9 months
Step-by-step explanation:
Given
Fabulous fitness charges a one-time fee of $90 and an additional $25 per month
let the number of months be x
and the total charges be y
y= 25x+90---------1
Wonder weights charges a one-time fee of only $ 27 dollars but charge an additional $32 each month
let the number of months be x
and the total charges be y
y= 32x+27------------2
Required
The value of x, that is the number of months
Step two:
Equating both equations we have
25x+90=32x+27
collect like terms
25x-32x=27-90
-7x=-63
7x=63
divide both sides by 7
x= 63/7
x= 9 months
24 = -3 + 3n
b.
11 + 4x = x - 10
c.
-216 = 1 + 7(1 + 8m)
d.
3p - 3(2 - 2p) = 34 + 4p
You must show all of your work to receive credit.
I will give you 27 points if you solve this by showing your work plz
Answer:
A) n=9
B)X=-7
C)m=-4
D)P=8
Step-by-step explanation:
A)24=-3+3n
move variable to the lefthand side &change its sign
-3n+24=-3
move the constant to the righthand side &change its sign
-3n=-3-24
calculate the difference
-3n=-27
devide both sides by-3
Solution:
n=9
B)11+4x=x-10
11+4x-x=-10
move variable to the lefthand side &change its sign
4x-x=-10-11
move constant to the righthand &change its sign
4x-x=-10-11
collect like terms
3x=-21
devide both sides of the equation by 3
solution :
x=-7
C)-216=1+7(1+8m)
multiply the parentheses by 7
-216=1+7+56m
add the numbers
-216=8m+56m
move variable to the lefthand side &change its sign
-56m-216=8
move constant to the righthand side &change its sign
-56m=8+216
add the numbers
-56m=224
devide both sides of the equation by -56
solution:
m=-4
D)3p-3(2-2p)=34+4p
multiply the parentheses by -3
3p-6+6p=34+4p
collect like terms
9p-6=34+4p
move the variable to the lefthand side &change its sign
9p-4p-6=34
move the constant to the righthand side &change its sign
9p-4p=34+6
collect like terms &calculate the sum
5p=40
devide both sides by 5
solution:
P=8
HiI hope this helps..